‘Sink or Swim’: A Qualitative Study to Understand How and Why Nurses Adapt to Support the Implementation of Integrated Diabetes Care - Fiona Riordan; Niamh McGrath; Sean F. Dinneen; Patricia M. Kearney; Sheena M. McHugh (International Journal of Integrated Care, 2019)
Background: Integrated care, organising care delivery within and between services, is an approach to improve the quality of care. Existing specialist roles have evolved to work across settings and services to integrate care. However, there is limited insight into how these expanded roles are implemented, including how they may be shaped by context. This paper examines how new diabetes nurse specialists working across care boundaries, together with hospital-based diabetes nurse specialists, adapt to support the implementation of integrated care. Methods: We conducted semi-structured focus groups and interviews with diabetes nurse specialists purposively sampled by work setting and health service region (n = 30). Analysis was data-driven, coding actions or processes to stay closer to the data and using 'In Vivo' codes to preserve meaning. Findings: Community nurse specialists described facing a choice of “sink or swim” when appointed with limited guidance on their role. To ‘swim’ and implement their role, required them to use their initiative and adapt to the local context. When first appointed, both community and hospital nurse specialists actively managed misconceptions of their role by other staff. To establish clinics in general practices, community nurse specialists capitalised on professional contacts to access GPs who might utilise their role. They built GP trust by adopting practice norms and responding to individual needs. They adapted to the lack of a multidisciplinary team “safety net” in the community, by “practicing at a higher level”, working more autonomously. Developing professional links and pursuing on-going education was a way to create an alternative ‘safety net’ so as to feel confident in their clinical decision-making when working in the community. Workarounds facilitated information flow (i.e. patient blood results, treatment, and appointments) between settings in the absence of an electronic record shared between general practices and hospital settings. Conclusions: Flexibility and innovation facilitates a new way of working across boundaries. Successful implementation of nurse specialist-led integrated care requires strategies to address elements in the inner (differences in practice organisation, role acceptance) and outer (information systems) context.